2002
DOI: 10.1287/msom.4.3.171.7754
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and Flexibility in Supply Contracts with Options

Abstract: We investigate the role of options (contingent claims) in a buyer-supplier system. Specifically using a two-period model with correlated demand, we illustrate how options provide flexibility to a buyer to respond to market changes in the second period. We also study the implications of such arrangements between a buyer and a supplier for coordination of the channel. We show that, in general, channel coordination can be achieved only if we allow the exercise price to be piecewise linear. We develop sufficient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
237
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(249 citation statements)
references
References 13 publications
0
237
0
Order By: Relevance
“…A basic review of these results can be found in Cachon (2003), Kleindorfer and Wu (2003), Swaminathan and Tayur (2003). Linking this literature with the options framework here, several papers (Araman et al 2002, Barnes-Schuster et al 2002, Shi et al 2002 show that buy-back contracts, quantity-flexible contracts, information-sharing contracts, as well the classic newsvendor model and others are all special cases of two-part-tariff options (however, these papers only treat the single-seller, single-buyer case).…”
Section: Literature Reviewmentioning
confidence: 89%
“…A basic review of these results can be found in Cachon (2003), Kleindorfer and Wu (2003), Swaminathan and Tayur (2003). Linking this literature with the options framework here, several papers (Araman et al 2002, Barnes-Schuster et al 2002, Shi et al 2002 show that buy-back contracts, quantity-flexible contracts, information-sharing contracts, as well the classic newsvendor model and others are all special cases of two-part-tariff options (however, these papers only treat the single-seller, single-buyer case).…”
Section: Literature Reviewmentioning
confidence: 89%
“…This insight was apparently first explored in Barnes-Schuster et al (2002), where the authors show that backup agreements, QF contracts, and pay-to-delay contracts are special cases of their options-embedded model (one seller, one buyer, two period).…”
Section: Kleindorfer and Wu Integrating Contracting With B2b Exchangesmentioning
confidence: 98%
“…In particular, some papers study option contracts, e.g., Barnes-Schuster et al [1] or Eppen and Iyer [6]. More relevant to our model are papers that analyze the behavior of suppliers in offering options to a buyer, the prelude to introducing competition between suppliers.…”
Section: Literature Reviewmentioning
confidence: 99%